2020
DOI: 10.1159/000510146
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Light Spectra on the Production of Cannabinoids

Abstract: In recent years, more attention has been paid to cannabis from both medical and political points of view. This study investigates the influence of 5 different light spectra on the active substance content in THC-poor hemp of the Alessia chemotype II variety. The focus is on comparing conventional growing under metal halide lamps with growing under high-pressure sodium (HPS) vapor lamps with regard to different spectra of LED lighting modules. Growing was carried out in 10 growing boxes under controlled and mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…Increasing the blue-light fraction has conflicting results in CBD-dominant (fiber-type) chemotypes. Some studies report no significant impact of light spectrum on CBD biosynthesis [ 17 , 34 ], whereas others did report a significant change in CBD concentration for plants grown under a higher blue-light fraction [ 18 , 25 , 33 ]. Studies reporting increased CBD concentration with an increase in blue-light fractions did compare treatment with different PPFD levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increasing the blue-light fraction has conflicting results in CBD-dominant (fiber-type) chemotypes. Some studies report no significant impact of light spectrum on CBD biosynthesis [ 17 , 34 ], whereas others did report a significant change in CBD concentration for plants grown under a higher blue-light fraction [ 18 , 25 , 33 ]. Studies reporting increased CBD concentration with an increase in blue-light fractions did compare treatment with different PPFD levels.…”
Section: Discussionmentioning
confidence: 99%
“…Fixture efficacy plays an important role in C. sativa production as lighting represents one of the highest operating costs and associated environmental performance [ 22 ]. The impact of the light spectrum on C. sativa cultivation has been reported with different lighting systems, including HPS [ 23 , 24 ] and LEDs [ 25 , 26 , 27 ]. These studies concluded that blue light led to increased cannabinoid concentration (% w/w ), while supplemental green light-induced both cannabinoid and terpene accumulation [ 17 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation